A realidade factual e o dever ser : as percepções dos professores de educação física Xavante sobre “sua” formação inicial - Freitas, Gibran Dias Paes de (2020)
This dissertation developed in the Indigenous Land of São Marcos; Villages Nossa Senhora de Guadalupe, Nossa Senhora de Fátima, Nossa Senhora da Guia e São Marcos; seeks to comprehend the perceptions about the initial formation of Xavante Indigenous Physical Education teachers, through interviews, from the indigenous state schools in the mentioned villages based on the intercultural categories, universal and local knowledge, limits and possibilities of pedagogical practice based on initial training and didactic knowledge about physical education. Over the chapters, comprehensions and perceptions about Barra do Garça’s Xavante population are presented, taking into consideration its history, socio-cultural aspects, tracing the wanderings and battles fought until reaching São Marcos Indigenous Land, the relationships that were built along with this process, its presence in Barra do Garças’s daily life, how the relations between indigenous and non-indigenous people are built, establishing such a context in the historical construction of the city, its current conjunction and the perception of non-indigenous people about indigenous people, thus building the limits of a civilizing frontier between cultures that occupy the same territory. Thus, we appropriated the concepts of “civilizing process” from a colonizing view, “decoloniality” and “territory, space and place”, with a view to overcoming the colonial perspective of indigenous school education. The historical context of indigenous school education in Brazil and in Mato Grosso and the debate about the legal matter of indigenous school education, bringing as the bottom line the promulgation of the Federal Constitution of 1988 and the laws published since then. It also addressed the current context of the initial training of indigenous teachers in Brazil, in Mato Grosso and Barra do Garças, the limits and possibilities faced in the current situation. The results point to the need to rethink the initial training of indigenous teachers in Brazil, Mato Grosso and Barra do Garças, concerning the still existing deficiency in the number of teachers without a degree in teaching, considering that the policies of University education have made little progress, thus having access to training in elementary education, in the subjects' speeches it is evident the configuration of a functional intercultural training and physical education emptied of criticality about the body culture of indigenous and non-indigenous movements, with actions by teachers and the school that seek to overcome this situation and value their body practices and cosmologies on the school floor. Based on these questions, the data analysis points to the understanding of the subjects' perception regarding the formation in Intercultural Teaching as an initial training proposal based on the categories already listed.